Measures to assess the performance of an Australian non-government charitable non-acute health service: A Delphi Survey of Organisational Stakeholders. (February 2018) - Colbran, Richard; Ramsden, Robyn; Stagnitti, Karen; Adams, Samantha
Organisation performance measurement is relevant for non-profit charitable organisations as they strive for security in an increasingly competitive funding environment. This study aimed to identify the priority measures and indicators of organisational performance of an Australian non-government charitable organisation that delivers non-acute health services. Seventy-seven and 59 participants across nine stakeholder groups responded to a two-staged Delphi technique study of a case study organisation. The stage one questionnaire was developed using information garnered through a detailed review of literature. Data from the first round were aggregated and analysed for the stage two survey. The final data represented a group consensus. Quality of care was ranked the most important of six organisational performance measures. Service user satisfaction was ranked second followed by financial performance, internal processes, employee learning and growth and community engagement. Thirteen priority indicators were determined across the six measures. Consensus was reached on the priority organisational performance measures and indicators. Stakeholders of the case study organisation value evidence-based practice, technical strength of services and service user satisfaction over more commercially orientated indicators.